Development of Hybrid Data Security System using LSB Steganography and AES Cryptography - Seddeq E. Ghrare; Maisem A. Abouras; Ibrahim A. Akermi (African Journal of Advanced Pure and Applied Sciences, 2024)
With the rapid advancement in communication and information technologies, the volume of data shared online has witnessed exponential growth. Consequently, securing sensitive and confidential information has become imperative. Various techniques, including steganography, coding, and cryptography, are employed to protect such data. In this paper, we propose an efficient method that combines Advanced Encryption Standard (AES) cryptography with Least Significant Bit (LSB) image steganography. We begin by concealing the secret data within a cover image using the LSB technique. The steganographic image is created by embedding the secret data in the least significant bits of pixel values. Next, we apply the AES algorithm to encrypt the steganographic image, providing a higher level of security. The strength of our system lies in the dual application of cryptography and steganography. Cracking this cryptosystem requires breaking both the encryption and decryption keys, and extracting the hidden data which is considered difficult to achieve. Our experiments demonstrate that the proposed system achieves superior security and better steganographic image quality.